Predicting understory maximum shrubs cover using altitude and overstory basal area in different Mediterranean forests - Coll, Lluís; González-Olabarria, José Ramón; Mola-Yudego, Blas; Pukkala, Timo; Messier, Christian (European Journal of Forest Research, 2010)
In some areas of the Mediterranean basin where the understory stratum represents a critical ﬁre hazard, managing the canopy cover to control the understory shrubby vegetation is an ecological alternative to the current mechanical management techniques. In this study, we determine the relationship between the overstory basal area and the cover of the understory shrubby vegetation for different dominant canopy species (Pinaceae and Fagaceae species) along a wide altitudinal gradient in the province of Catalonia (Spain). Analyses were conducted using data from the Spanish National Forest Inventory. At the regional scale, when all stands are analysed together, a strong negative relationship between mean shrub cover and site elevation was found. Among the Pinaceae species, we found fairly good relationships between stand basal area and the maximum development of the shrub stratum for species located at intermediate elevations (Pinus nigra, Pinus sylvestris). However, at the extremes of the elevationclimatic gradient (Pinus halepensis and Pinus uncinata stands), stand basal area explained very little of the shrub cover variation probably because microsite and topographic factors override its effect. Among the Fagaceae species, a negative relationship between basal area and the maximum development of the shrub stratum was found in Quercus humilis and Fagus sylvatica dominated stands but not in Quercus ilex. This can be due to the particular canopy structure and management history of Q. ilex stands. In conclusion, our study revealed a marked effect of the tree layer composition and the environment on the relationship between the development of the understory and overstory tree structure. More ﬁne-grained studies are needed to provide forest managers with more detailed information about the relationship between these two forest strata.
Keywords: á altitude á; á fagaceae; Altitude; Basal area; e47; european network for forest; Fagaceae; Overstory; overstory á basal area; Pinaceae; Shrub cover; shrub cover á pinaceae; the cost action; the final conference of; this article originates from; vegetation management

Predicting stand damage and tree survival in burned forests in Catalonia (North-East Spain) - González Ramón, José; Trasobares, Antoni; Palahí, Marc; Pukkala, Timo (Ann. For. Sci., 2007)
The study developed models for predicting the post-fire tree survival in Catalonia. The models are appropriate for forest planning purposes. Two types of models were developed: a stand-level model to predict the degree of damage caused by a forest fire, and tree-level models to predict the probability of a tree to survive a forest fire. The models were based on forest inventory and fire data. The inventory data on forest stands were obtained from the second (1989-1990) and third (2000-2001) Spanish national forest inventories, and the fire data consisted of the perimeters of forest fires larger than 20 ha that occurred in Catalonia between the 2nd and 3rd measurement of the inventory plots. The models were based on easily measurable forest characteristics, and they permit the forest manager to predict the effect of stand structure and species composition on the expected damage. According to the stand level fire damage model, the relative damage decreases when the stand basal area or mean tree diameter increases. Conversely, the relative stand damage increases when there is a large variation in tree size, when the stand is located on a steep slope, and when it is dominated by pine. According to the tree level survival models, trees in stands with a high basal area, a large mean tree size and a small variability in tree diameters have a high survival probability. Large trees in dominant positions have the highest probability of surviving a fire. Another result of the study is the exceptionally good post-fire survival ability of Pinus pinea and Quercus suber.
Keywords: damage model; fire management; logistic function; survival model; tree mortality